Production and Compatibility Assessment of Denitrifying Biogranules Tailored for Self-Healing Concrete Applications - Sonmez, Merve; Ersan, Yusuf Cagatay (Elsevier Sci Ltd, 2022)
Microbial granules have been mostly used for wastewater treatment. Recently, biogranules consisting nitrate-reducing microorganisms have appeared as a unique healing agent providing simultaneous self-healing of cracks and corrosion inhibition of rebar in concrete. Yet, information about the production process and microbial activity of these biogranules as well as their compatibility with cementitious materials remains unknown. This study presents the biogranule production procedure in detail and evaluates the compatibility of the produced biogranules with the cementitious composites. In the form of biogranules, bacteria doses varying between 0.25% and 3.00% w/w cement were incorporated into mortar and the variations in fresh and hardened properties of mortars were evaluated with respect to abiotic mortars. Biogranules were also tested for their compatibility with concrete at minimum and the defined maximum tolerable doses. Biogranules with a NOx-N reduction activity of 0.10 g NOx-N.g(-1) bacteria.d(-1) and organic carbon oxidation activity of 1.50 g HCOO-.g(- 1) bacteria.d(-1) were produced successfully by using minimal medium. It was found out that biogranules enable bacteria incorporation into mortar up to a dose of 2.50% w/w cement without compromising fresh and hardened properties of cementitious composites. It was revealed that the compatibility of the biogranules was due to the mineral layer surrounding the biogranules which prevented interaction between the cement matrix and the microbial content. The thickness of the protective mineral layer around the granules was varying between 50 and 300 mu m depending on the granule size. Net yield for concrete compatible biogranule production was determined as 0.05 g bio-granule.g(-1)HCOO-.
Sonmez Tugluca, Merve/0000-0002-5197-4863;
Keywords: Bacteria-Based Self-Healing; Granule Content; Aerobic Granular Sludge; Micp; Nitrate Reduction